Humanized mouse G6 anti-idiotypic monoclonal antibody has therapeutic potential against IGHV1-69 germline gene-based B-CLL. Issue 4 (18th May 2016) - Chang, De-Kuan; Kurella, Vinodh B.; Biswas, Subhabrata; Avnir, Yuval; Sui, Jianhua; Wang, Xueqian; Sun, Jiusong; Wang, Yanyan; Panditrao, Madhura; Peterson, Eric; Tallarico, Aimee; Fernandes, Stacey; et al.
ABSTRACT: In 10–20% of the cases of chronic lymphocytic leukemia of B-cell phenotype (B-CLL), the IGHV1-69 germline is utilized as VH gene of the B cell receptor (BCR). Mouse G6 (MuG6) is an anti-idiotypic monoclonal antibody discovered in a screen against rheumatoid factors (RFs) that binds with high affinity to an idiotope expressed on the 51p1 alleles of IGHV1-69 germline gene encoded antibodies (G6-id + ). The finding that unmutated IGHV1-69 encoded BCRs are frequently expressed on B-CLL cells provides an opportunity for anti-idiotype monoclonal antibody immunotherapy. In this study, we first showed that MuG6 can deplete B cells encoding IGHV1-69 BCRs using a novel humanized GTL mouse model. Next, we humanized MuG6 and demonstrated that the humanized antibodies (HuG6s), especially HuG6.3, displayed ∼2-fold higher binding affinity for G6-id + antibody compared to the parental MuG6. Additional studies showed that HuG6.3 was able to kill G6-id + BCR expressing cells and patient B-CLL cells through antibody-dependent cell-mediated cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC). Finally, both MuG6 and HuG6.3 mediate in vivo depletion of B-CLL cells in NSG mice. These data suggest that HuG6.3 may provide a new precision medicine to selectively kill IGHV1-69 -encoding G6-id + B-CLL cells.